ETNOMATEMATIKA PADA KESENIAN MUSIK PATROL KELABANG SONGO PROBOLINGGO SEBAGAI MEDIA BELAJAR MATEMATIKA - Indah Puspa Sari; Nuryami (LPPM Institut Ahmad Dahlan Probolinggo, 2024)
There is a lot of cultural diversity in Indonesia, one of which is the art of the Songo Kelabang Patrol Music in Probolinggo, reflecting local cultural values. Education and culture are interrelated, and to preserve this art, an ethnomathematics approach is used to explore the relationship between culture, environment, and mathematics. This research aims to introduce and preserve this art through ethnomathematics as a mathematics learning medium, provide new insight into local culture, and create potential as a mathematics learning medium inside and outside the classroom. This qualitative research uses observation and literature study as data collection techniques. The results show that there are mathematical elements in the design of the Kelabang Songo Patrol transport cart and musical instruments, such as gongs, demands, genders, drums, and tong tongs. This connection can be used as an alternative mathematics learning media, especially in the context of geometry. This research is expected to provide benefits for students and educators, with suggestions for further research exploring aspects of musical rhythm and other activities as a means of student learning.Keywords: Ethnomathematics; Songo Centipede; Geometry